In Search for a Better Tuberculosis Diagnostic Test - Antônio Campos-Neto (Hospital de Clínicas de Itajubá, 2016)
Tuberculosis (TB) remains one of the most common deadly infectious diseases on the planet and the diagnosis, treatment and prevention of this disease present serious global public health challenges.1 The TB treatment regimen takes too long to cure and is complicated to administer, and anti-TB drugs can be toxic.2 There is no efficacious vaccine for TB.3   Rates of new infections are still rising in many endemic areas where TB co-infects those with HIV/AIDS.4 Treating this co-infection is further complicated by the surge of multi-drug resistant strains of Mycobacterium tuberculosis (Mtb).5 TB diagnosis remains antiquated and inadequate in most parts of the world.6,7 Given that one-third of the world's population is assumed to have been exposed to Mtb and to have developed latent infection, diagnostic assays based on the host immune response (whether cellular or humoral) often fail to distinguish active TB from latent cases.8,9   Unfortunately, identifying individuals with active pulmonary disease (the source of disease transmission) and distinguishing them from those with latent (non-transmissible) infection is critical to provide prompt and appropriate therapy to minimize the spread of TB.  Active pulmonary TB is typically diagnosed by finding Mtb in sputum by acid-fast smear, a labor-intensive process requiring trained personnel and with widely varied sensitivity in different settings (20-60%).